The adventures of Ibn Battuta, a Muslim traveler of the 14th century - Dunn, Ross E. (University of California Press, 2005)
A retelling of a great traveler's remarkable career, presented within the cultural and social context of Islamic society as both a biography of an extraordinary personality and a study of the hemispheric dimensions of human interchange in medieval times.